Mapping research on peace education: the bibliometric analysis for research agenda in the future - Saputra, Wahyu Nanda Eka; Rohmadheny, Prima Suci; Hidayah, Nur; Handayani, Trikinasih; Supriyanto, Agus; Agungbudiprabowo, Agungbudiprabowo (Institute of Advanced Engineering and Science, 2025)
This study aims to analyze the trend of scientific publications with the theme of peace education. This study uses bibliometric analysis to describe trends in peace education research and reveal its bibliometric profile. The data was taken from the Scopus database covering 1961 to 2023 with the keywords “peace education” and “violence.” The results of the analysis show that there is a positive trend toward an increase in publications with the theme of peace education. The most prominent country that contributes to peace educationthemed publications is the United States. The University of Toronto and the University of Kwazulu-Natal are the most famous universities that publish research results on peace education. The Journal of Peace Education is the favorite journal for publication on the theme of peace education. Vaughn Mitchell John and Johan Galtung are prominent names who have influenced publications on peace education. Potential themes regarding peace education are discussed in this paper. This research contributes to analyzing structure, trends, collaboration opportunities, and research roadmaps as a basis for future research.